Managing Conflicts of Interest in the UK National Institute for Health and Care Excellence (NICE) Clinical Guidelines Programme: Qualitative Study - Graham, Tanya; Alderson, Phil; Stokes, Tim (PloS one, 2015)
There is international concern that conflicts of interest (COI) may bias clinical guideline development and render it untrustworthy. Guideline COI policies exist with the aim of reducing this bias but it is not known how such policies are interpreted and used by guideline producing organisations. This study sought to determine how conflicts of interest (COIs) are disclosed and managed by a national clinical guideline developer (NICE: the UK National Institute for Health and Care Excellence). Qualitative study using semi-structured telephone interviews with 14 key informants: 8 senior staff of NICE's guideline development centres and 6 chairs of guideline development groups (GDGs). We conducted a thematic analysis. Participants regard the NICE COI policy as comprehensive leading to transparent and independent guidance. The application of the NICE COI policy is, however, not straightforward and clarity could be improved. Disclosure of COI relies on self reporting and guideline developers have to take "on trust" the information they receive, certain types of COI (non-financial) are difficult to categorise and manage and disclosed COI can impact on the ability to recruit clinical experts to GDGs. Participants considered it both disruptive and stressful to exclude members from GDG meetings when required by the COI policy. Nonetheless the impact of this disruption can be minimised with good group chairing skills. We consider that the successful implementation of a COI policy in clinical guideline development requires clear policies and procedures, appropriate training of GDG chairs and an evaluation of how the policy is used in practice.